Variant surface glycoprotein synthesis and cell cycle progression in Trypanosoma brucei - Wand, N; Nadina Wand (2011)
The unicellular eukaryote Trypanosoma brucei causes African Sleeping sickness and multiplies extracellularly in the bloodstream of the infected host. The parasite evades antibody-mediated lysis by switching its Variant Surface Glycoprotein (VSG) coat. Blocking VSG synthesis results in an abrupt growth inhibition and a precise pre-cytokinesis cell cycle arrest, with an accumulation of cells with two nuclei and two kinetoplasts. Additionally, induction of VSG RNAi triggers a global block in translation, which is not due to a general decrease in transcript levels. The mechanism behind this translation arrest was investigated. It was observed that it correlated with a decrease in polysomes, indicating that translation was blocked at the level of initiation. It was also shown that the VSG RNAi-triggered growth inhibition was reversible, which suggests that this is not a lethal phenotype. The VSG221 RNAi-induced growth arrest could be alleviated if a second different VSG (VSG117), which was not recognised by the VSG221 RNAi, was expressed immediately downstream of the promoter of the active VSG221 Expression site. Further, it was possible to delete the telomeric VSG221 in these VSG double-expressors, leaving the cells completely reliant on the second complementing VSG117 gene. VSG117 expressed from a promoter-adjacent position in the active Expression site was shown to form a functional surface coat that protected the parasites from complement-mediated lysis in vitro. Transiently transfecting cells with anti-VSG221 morpholino oligonucleotides allowed us to specifically block translation of VSG221 mRNA without degrading it. This resulted in a pre-cytokinesis cell cycle arrest similar to that induced by VSG221 RNAi. This indicates that the VSG RNAi-triggered growth inhibition was due to a lack of VSG protein or its synthesis rather than the ablation of the abundant VSG mRNA. In addition, it was shown that blocking VSG synthesis reduced the rate of surface VSG internalisation in cells that were stalled precytokinesis, but had no effect on other endocytic markers. These experiments give us further insight into the importance of the protective VSG coat for pathogenicity in T. brucei.